Water column raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M197 - Browning, Thomas J; Achterberg, Eric Pieter; Wilckens, Henriette; Bialik, Or M; Schumacher, Mia (PANGAEA, 2024)
Raw water column data were collected aboard RV METEOR during cruise M197 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 30.12.2023 - 06.02.2024 from Limassol (Republic of Cyprus) to Catania (Italy) in the Mediterranean. The overarching aim was to use the rapidly changing Eastern Mediterranean Sea (EMS) as a natural laboratory to gain mechanistic understanding of biogeochemical and ecosystem transitions of a future (sub-)tropical ocean affected by global warming and other anthropogenic pressures. The M197 cruise on RV Meteor has the following objectives: (i) characterising nutrient biogeochemistry and phytoplankton nutrient limitation of seawaters in the Eastern Mediterranean Sea, (ii) documenting in detail the microbial communities that inhabit these waters from the surface ocean to sediments, (iii) assessing mechanistic connections between nutrient biogeochemistry, surface ocean productivity, deeper water metabolism, and shelf sediments in the cycling of carbon and major nutrients, (iv) using the sedimentary record to assess past environmental change in the EMS. Data were recorded within the EEZs of Greece and Cyprus. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.
Keywords: Bathymetry; Multibeam